2020
DOI: 10.1101/2020.11.26.20238923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered anterior default mode network dynamics in progressive multiple sclerosis

Abstract: Functional reorganization at the progressive stage of multiple sclerosis has received limited attention, despite the fact that functional changes are known to occur. Characterizing large-scale network dynamics at rest has the potential to provide new insights into the complexity of such functional alterations. In this case-control study, we explored the dynamic properties of large-scale functional networks during rest in 25 healthy controls and 32 patients with progressive multiple sclerosis, using the innovat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…for a large number of subjects. Previous findings based on iCAPs have for instance revealed organizational principles of brain function during rest (18) and sleep (102) in healthy controls, next to alterations in 22q11ds ( 103) and multiple sclerosis (104). Next to CAPs-inspired approaches, dynamic functional connectivity has recently been investigated with the use of cofluctuations and edgecentric techniques (105)(106)(107)(108)(109).…”
Section: O R I Gmentioning
confidence: 99%
See 1 more Smart Citation
“…for a large number of subjects. Previous findings based on iCAPs have for instance revealed organizational principles of brain function during rest (18) and sleep (102) in healthy controls, next to alterations in 22q11ds ( 103) and multiple sclerosis (104). Next to CAPs-inspired approaches, dynamic functional connectivity has recently been investigated with the use of cofluctuations and edgecentric techniques (105)(106)(107)(108)(109).…”
Section: O R I Gmentioning
confidence: 99%
“…In addition, decoding of the deconvolved spontaneous events allows to decipher the flow of spontaneous thoughts and actions across different cognitive and sensory domains while at rest (18,22,23). Beyond findings on healthy subjects, deconvolution techniques have also proven their utility in clinical conditions to characterize functional alterations of patients with a progressive stage of multiple sclerosis at rest (24), to find functional signatures of prodromal psychotic symptoms and anxiety at rest on patients suffering from schizophrenia 25), to detect the foci of interictal events in epilepsy patients without an EEG recording (17,26), or to study functional dissociations observed during nonrapid eye movement sleep that are associated with reduced consolidation of information and impaired consciousness (27).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, decoding of the deconvolved spontaneous events allows to decipher the flow of spontaneous thoughts and actions across different cognitive and sensory domains while at rest (Karahanoglu and Ville 2015;Gonzalez-Castillo et al 2019;Tan et al 2017). Beyond findings on healthy subjects, deconvolution techniques have also proven its utility in clinical conditions to characterize functional alterations of patients with a progressive stage of multiple sclerosis at rest (Bommarito et al 2020), to find functional signatures of prodromal psychotic symptoms and anxiety at rest on patients suffering from schizophrenia (Zöller et al 2019), to detect the foci of interictal events in epilepsy patients without an EEG recording (Lopes et al 2012;, or to study functional dissociations observed during non-rapid eye movement sleep that are associated with reduced consolidation of information and impaired consciousness (Tarun et al 2020).…”
Section: Introductionmentioning
confidence: 99%